Cardiac and vascular complications in lupus: Is there a role for sex? - Corker, Alexa; Learmonth, Maya; Patrick, David M.; DeLeon-Pennell, Kristine Y.; Van Beusecum, Justin P. (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is a common systemic autoimmune disorder and is characterized by autoantibody formation and subsequent immune complex deposition into target organs. SLE affects nearly 9 women to every 1 man worldwide. Patients with SLE are at an enhanced risk for cardiovascular disease (CVD) morbidity and mortality. CVD is the leading cause of death worldwide and includes heart and blood vessel disorders, cerebrovascular disease, and rheumatic heart disease. Specific mechanisms by which cardiac and vascular pathophysiology develops in patients with SLE are still not fully known. Not only do we not understand this correlation between SLE and CVD, but there is also a critical gap in scientific knowledge in the contribution of sex. In this review, we will discuss the cardiac and vascular pathological disease states that are present in some patients with SLE. More importantly, we will discuss the potential mechanisms for the role of sex and sex hormones the development of CVD with SLE.